Amadou Hampâté Bâ and the Reconstruction of the African Identity Through Orality - Álvarez Martínez, Teresa (Thélème. Revista Complutense de Estudios Franceses, 2014)
Amadou Hampâté Bâ (Bandiagara, 1901 – Abiyán, 1991), writer, ethnologist and historian, was one of the most relevant figures in African culture of the twentieth century. Defender and disseminator of the history and culture of Africa, his work as a member of the Executive Council of UNESCO allowed him to launch influential campaigns to conserve the immaterial cultural patrimony of West Africa. Hampâté Bâ was one of the first African ethnologists dedicated to the study and dissemination of African culture. His interpretation of the culture as a living entity without the prejudices deriving from colonialism was fundamental to the reconstruction of the African identity.